Renewable heating strategies and their consequences for storage and grid infrastructures comparing a smart grid to a smart energy systems approach. (15th May 2018) - Lund, Henrik
Abstract: This paper compares different strategies to transform the heating sector into a future 100% renewable energy solution. It focuses on the consequences for infrastructures in terms of grids and storage across the electricity, gas and heating sectors. The hypothesis is that these consequences are rarely taken into proper consideration, even though the costs are significant and differ substantially between the alternative pathways. While the smart grid scenarios are based on electricity as an energy carrier, the "smart energy systems" approach is based on a cross-sectoral use of all grids. Using Denmark as a case, this paper shows how the current gas and district heating grids each have twice the capacity of the electricity distribution grid. Moreover, the existing gas and thermal storage capacities are substantially higher and the additional future capacities are more affordable than within the electricity sector. The conclusion is that the "smart grid" pathway requires a 2–4 times expansion of the electricity grid and significant investments in electricity storage capacities, while the "smart energy systems" pathway can be implemented with relatively few investments in affordable minor expansions of existing grids and storage capacities. Highlights: Comparing different strategies to transform the heating sector to 100% renewables. Comparing a Smart Energy Systems to a Smart Grid approach. Focus is on the consequences for storage and grid infrastructures. Smart grids may require significant expansion of grid and storage infrastructures. Smart energy systems can succeed within existing grid and storage infrastructures.